Children’s existential questions and worldviews: possible RE responses to performance anxiety and an increasing risk of exclusion - Osbeck, Christina (Journal of Religious Education, 2024)
The aim of this article is to examine patterns in Swedish children’s existential questions and worldviews in 2020 in relation to patterns from 1970 and 1987, but also to point towards a further discussion of importance, about possible RE responses to these findings. The material, children’s texts, comes both from studies conducted by Sven Hartman and colleagues in the 1970s and 1980s, and from new empirical studies. The children’s responses are collected according to the same method, sentence completion tasks, in both cases. Theoretically, the article is anchored in both the tradition of Swedish worldview studies and the new international interest in these perspectives for religious education. Existential questions and worldviews are seen as interdependent in human beings’ life interpretations, which are continuously developing and are both sociocultural and existential in nature. The empirical findings show a strong and increasing focus on relationships, but also a recurrent focus on achievements, which relates to school as context and community. In relation to these findings, the article stresses the importance of RE responses, and discusses concretely what such responses might advantageously include. Among other things, the importance is stressed of an RE that offers the student greater awareness of her life interpretations, and encourages her to develop broader repertoires of frameworks, through which the student might have a better chance to be the author of her own life, which is inevitably a collectively shared life.